Resolving the Political Tension: How Online Photographs Portray Candidates in Nigeria’s 2015 Presidential Election - Obono, Koblowe (Covenant Journal of Communication, 2019)
This paper investigates the online pictorial portrayal of two frontline candidates in Nigeria’s 2015 presidential elections and how it resolved the related political tensions. Careful observation and analyses of the candidates’ photographs, in accordance with the social constructivist perspective, enabled the determination of their conduct and verbal communication in a social context. Findings show that candidates’ facial expression, body language, among others, portrayed mutual accord, cordiality and partnership. The impressions created from these did help to neutralize the perceived threats of violence from both sides of the political divide. In spite of the unpleasant rhetoric by the candidates on several occasions, the photographs portrayed them as friends as the images symbolized unity in diversity. One fact emerged from this study: When texts and rhetoric from political candidates and their supporters came like a flood, photographs were there to raise a standard against it.